Play to Win Golf - Feherty, David and Fine, Alan (London Octopus Books Ltd., 1987)
The book concentrates on the fundamentals of grip, stance, posture and the swing. It gives jargon-free advice complemented by detailed instructions.
Include Illustration, Index
Keywords: Golf